2020
DOI: 10.1108/ijmhsc-07-2020-0068
|View full text |Cite
|
Sign up to set email alerts
|

Narratives of internal migration experiences, health/well-being issues among females working as head-porters (Kayayei) in Ghana

Abstract: Purpose This study aims to explore the internal migration experiences and health/well-being issues of 38 girls and women working as Kayayei (head-porters) in Accra, Ghana. Design/methodology/approach Data were collected from seven focus group interview sessions, and thematic analysis was used to analyse the data. Findings The results revealed the geographic, structural and family issues that promote increased migration of females to the cities. The findings betray the potential negative effects of migratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Increases in the numbers of girls and young women migrating to cities have been particularly pronounced, with many girls taking-up work as head-porters (known as Kayayei). Many of these girls are poorly educated and are often exposed to multiple intersecting disadvantages that affect their health [ 6 , 31 ].…”
Section: Migration and Health In Ghanamentioning
confidence: 99%
See 3 more Smart Citations
“…Increases in the numbers of girls and young women migrating to cities have been particularly pronounced, with many girls taking-up work as head-porters (known as Kayayei). Many of these girls are poorly educated and are often exposed to multiple intersecting disadvantages that affect their health [ 6 , 31 ].…”
Section: Migration and Health In Ghanamentioning
confidence: 99%
“…Poor work and housing conditions place young migrants (both internal and international) at greater risk of contracting communicable diseases including malaria and sexually transmitted infections [ 6 , 30 ]. Access to health care services is also limited with evidence suggesting that few migrants in Ghana have access to appropriate health insurance and are unable to register for the National Health Insurance Scheme (NHIS) [ 32 , 33 ].…”
Section: Migration and Health In Ghanamentioning
confidence: 99%
See 2 more Smart Citations
“…Head porting in turn is serving as a pull factor attracting young girls from the rural areas of Ghana into the cities. Kuyini et al (2020) investigated the nexus between female migration, kayayei and health wellbeing and found that geolocation development inequality and family issues promote migration of young females from the rural to urban areas in Ghana. The study identified some adverse effects of such migration patterns on the quality of accessing health services by the young female immigrants.…”
Section: Literature Review 21 Migration Kayayei and Health Wellbeingmentioning
confidence: 99%